“Biotechnological approaches for conservation of the vulnerable Capparis spinosa var. aegyptia” - Sabha Salman Mustafa; Heba El-Sayed Ghareb (Discover Applied Sciences)
Abstract Saint Katherine Protectorate, one of the largest protected areas in Egypt, is home to a variety of rare and endangered species. Among them is Capparis spinosa var. aegyptia, a plant that is facing population decline due to two key factors; over-harvesting for traditional medicine and drought-induced stress. DNA barcoding analysis and in vitro culture techniques were conducted in this research for the first time to save this endangered variety, aligning with the United Nations Sustainable Development Goal 15 for ecosystem preservation and biodiversity conservation. PCR amplification and sequencing, utilizing DNA markers trnH-psbA, maturase K (matK), and ribulose-1, 5-bisphosphate carboxylase/oxygenase large subunit (rbcL), were used to authenticate the plant. BLAST results and phylogenetic analysis confirmed the identification of the plant. In vitro propagation of the plant was achieved by culturing stem nodal segments on Murashige and Skoog (MS) medium supplemented with various cytokinins and 0.5 mg/l of α-Naphthalene acetic acid (NAA). To enhance shoot multiplication, different cytokinin combinations were evaluated. The highest growth induction (95%) and mean number of shoots (11.2) were observed with MS medium containing 1 mg/l each of 6-benzyl adenine (BA) and kinetin (Kin). Multiple shoots were successfully rooted on quarter-strength (¼) MS medium fortified with 3.0 mg/l NAA. After rooting, the plants were transferred to pots containing a mixture of sand, soil, and peat moss, and acclimatized in a greenhouse with a survival rate of 95%. This study demonstrates the potential of in vitro culture as a short-term conservation technique to propagate the endangered C. spinosa var. aegyptia, and highlights the importance of preserving and restoring our terrestrial ecosystems for sustainable development.